Role of particle morphology in the yielding behavior of dense thermosensitive microgel suspensions - Jathavedan, Kiran Kaithakkal; Kanheerampockil, Fayis; Bhat, Suresh (Journal of Applied Polymer Science, 2019)
The yielding behavior of dense thermosensitive microgel suspensions of poly(N-isopropylacrylamide) with two different particle morphologies viz core-shell (CS) morphology and particles with uniform crosslink density were studied. Structural properties were examined using dynamic light scattering and yielding behavior was investigated by nonlinear oscillatory rheology. Suspensions of particles with uniform crosslinking density showed a typical hard sphere like behavior with the loss modulus (G `') exhibiting a single peak due to cage breaking while CS type particles shows a double yielding at different ranges of strain similar to that seen in attractive colloidal glasses. The first yielding process in CS microgels is interpreted as due to the disentanglement of the overlapped polymer chains from the shells of the neighboring microgels and the second yielding process due to the breakage of cages formed by neighboring microgel particles. Current study suggests that the interpenetration of polymer chains at high concentrations sets in an attractive like potential leading to double yielding phenomena in an otherwise purely repulsive system. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48625.